(untitled) (Baghdad Science Journal, 2024)
The Sip-39 pair’s galaxies have been investigated using photometric and spectroscopic methods; the observation data was collected from the SDSS’s Data Release (DR17) and fitted to ellipses through utilizing the Image Reduction and Analysis Facility (IRAF) with STSDAS Library using ELLIPS task. The surface brightness of the two galaxies in the pair, as well as total flux, ellipticities, major axis position angles, both vertical and horizontal shifts, isophotal shape factors (B4), magnitudes, and the star-forming rates (SFR), in addition to the astrometric parameters of the pair, were evaluated. It appeared through data analysis that the Sip-39 pair is a closely interacting pair with clear interaction signs, and it is deemed to be a physical system with enhanced SFR.